STRATEGI DAKWAH KULTURAL NAHDLATUL ULAMA DAN MUHAMMADIYAH DI KABUPATEN BANYUMAS - Abdul Basit (IAIN Purwokerto, 2011)
Conceptually, the cultural da'wa (preaching) of NU and Muham- madiyah are based on bilhikmah (wisdom) principle stated in Guran. Since it was founded, NU has applied that principle as it can be seen from the da'wa by Walisongo: whereas Muhammadiyah formally present cultural da'wa as a discourse in 2002. In the application, NU cultural da'wa in Banyumas Regency is focused on the process of purification and tajdid of Nahdliyin's religious understanding and attitudes, while Muhammadiyah cultural da'wa in Banyumas Regency is focused on the diversification of da'wa methods. In addition, NU cultural da'wa is appied through oral da'wa, written da'wa, and direct practice in the society. Similari methods of da'wa is also done my Muhammadiyah. However, socialization through the organization can be cieariy seen in Muhammadiyah cultural da'wa. Although there are some differences in the socialization and application, the strategy of cultural da'wa is relevan to be applied in the plural society such as in Indonesia because cultural da'wa promotes a da'wa which is peaceful, humanistic, and accommodating to local culture.